PELAKSANAAN ASAS KETERTIBAN UMUM DI PENGADILAN NASIONAL TERHADAP PUTUSAN BADAN ARBITRASE ASING (LUAR NEGERI) - Basarah, Mochamad (Sekolah Tinggi Hukum Bandung, 2010)
New York convention was designed to give international value to decision of arbitration and also has regulated two items in arbitration mechanism, that is to say recognition of arbitration clause, and also recognition and implementation of arbitration decision. National court of justice related to this mechanism will adapt itself to convention regulations. This case is possible to appear although every party has chosen substantive law from different countries to regulate their agreements, because court of justice can refuse arbitration decision if it is assumed to violate against public order.Keywords: New York Convention Â Principle of Public Order ÂÂ National Court of